The influence of oxygen in the photoexpansion of GaGeS glasses - Messaddeq, S. H.; Mastelaro, V. R.; Li, M. S.; Tabackniks, M.; Lezal, D.; Ramos, A.; Messaddeq, Younes [UNESP] (Elsevier B.V., 2003)
Irreversible photoexpansion and photobleaching effect has been observed in amorphous Ga10Ge25S65 glass when its surface was exposed to light with energy greater than the band gap, 3.52 eV. The magnitude of the expansion of GaGeS glasses depends on the exposure conditions. Extended X-ray absorption fine structure (EXAFS) spectroscopy and Rutherford backscattering spectrometry (RBS) have been used to identify the chemical nature of the glass samples before and after illumination. The quantitative analysis of the EXAFS data leads to a two-shell model of 0.5 oxygen atoms at 2.01 Angstrom and 3.6 sulfur atoms at a 2.20 Angstrom. RBS technique demonstrated that chemical composition of the glass surface after irradiation is oxygen rich. The existence of Ge-O bonds in the glass after illumination was also confirmed by infrared measurements. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: chalcogenide glasses; photoexpansion; oxygen; EXAFS; RBS